Examining Project-Based Learning to Foster Creative Writing: Evidence from Indonesian Secondary Classrooms - Siti Syafi'atul Qomariyah; Indara Wahyudi; Dira Permana; Heri Hidayatullah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Project-Based Learning (PJBL) has been widely adopted to address various instructional challenges in English as a Foreign Language (EFL) classroom. However, its specific impact on students’ creative writing performance in Indonesian secondary education remains underexplored. This study aims to examine the effectiveness of PJBL in enhancing secondary students’ creative writing skills, particularly in higher-order language production. Employing a quasi-experimental design, the study involved 72 eleventh-grade students who were assigned to experimental and control groups. The experimental group received project-based writing instruction, while the control group was taught using conventional, teacher-centered methods. Data were collected through a creative writing test and analyzed using an independent samples t-test. The results revealed a statistically significant difference between the two groups, indicating that students exposed to PJBL demonstrated higher levels of creativity, idea development, and linguistic expression than those in the control group. These findings extend constructivist and sociocultural perspectives by illustrating how project-based tasks facilitate creative language use through collaboration, autonomy, and authentic learning experiences. Pedagogically, this study highlights PJBL as an effective instructional approach for fostering creative writing in EFL contexts and provides practical implications for teachers and curriculum developers seeking to promote creativity-oriented language instruction.